GLOBALIZATION AND EDUCATION- A CRITICAL INQUIRY - Ms. Sarbani Guha Ghosal (Galaxy International Interdisciplinary Research Journal, 2021)
Education in the world is always a matter of serious debate. The forces of globalization and liberalization since last quarter of earlier century has brought serious contentious issues regarding teaching and learning in forefront, particularly for developing economies with huge social divisions like us. The article tries to situate some of the issues of Indian educational sector in the context of international developments and have attempted to throw some lights in the journey to find out pragmatic strategies. Of course, a brief analysis of pandemic related problems is also included.